Supervision Of School Administrative Staff Competence To Improve School Administration Quality In Public High Schools - Nelfi Lidyanti; Asti Putri Kartiwi; Manap Somantri (International Journal of Educational Management and Innovation, 2023)
The background of this study is based on the need for more  attention to the competencies possessed by school administration personnel,  while administrative personnel is one of the pillars of school administrative services. The purpose of this study is to describe the planning, implementation, evaluation, and follow-up of supervision of school administrative personnel by school principals. The research method used is a qualitative descriptive approach. Data collection techniques in this study used observation, interviews, and documentation—analysis techniques through data collection, data reduction, conclusion-making, and triangulation. The results showed that the technical competence of the administrative staff at SMP Negeri Remban is quite good because they have good communication and always work together to expedite their work. In terms of role, the principal has played a role in improving the technical competence of administrative staff; this is indicated by the principal often taking the time to talk to the administrative staff so there is no awkwardness or fear between the principal and administrative staff; the principal also often holds meetings with administrative staff so that cooperation and communication between principals, teachers, and administrative staff are always well established. This research implies that the principal and education staff are an inseparable unit. Therefore it is hoped that good cooperation and communication between the two elements is expected so that in a future implementation, evaluation can be used as a guide as a follow-up if deficiencies are to be corrected.